Inhibition of the specific binding of human lactotransferrin to human peripheral-blood phytohaemagglutinin-stimulated lymphocytes by fluorescein labelling and location of the binding site. - Legrand, D (1991)
Labelling of human lactotransferrin with fluorescein 5'-isothiocyanate (FITC) in an equimolar ratio inhibits the binding of the protein to phytohaemagglutinin-activated human peripheral-blood lymphocytes. Therefore it can be assumed that FITC reacts at, or near, the receptor-binding site. Three FITC-labelled peptides have been purified from a tryptic digest of the FITC-labelled lactotransferrin. The determination of their amino acid sequence and their localization on the primary structure of the protein permitted the identification of two FITC-accessible areas in the N-terminal lobe and one in the C-terminal lobe. In fact, only 10% of the total FITC was conjugated to one lysine residue (Lys579) of the C-terminal lobe, whereas most (80%) of the FITC was conjugated to three close lysine residues [Lys263 (65% of total fluorescence), Lys280 and Lys282 (15% of total fluorescence)] located in beta-turn structures, of the N-terminal domain I of human lactotransferrin. The results obtained show that the receptor-binding site should be located in the vicinity of the FITC-accessible Lys263, Lys280 and Lys282, and corroborate our preliminary results reporting the involvement of the N-terminal domain I in the binding of human lactotransferrin to mitogen-stimulated lymphocytes [Rochard, Legrand, Mazurier, Montreuil & Spik (1989) FEBS Lett. 255, 201-204]. In any case, FITC labelling is not suitable for studying the binding of lactotransferrin to activated lymphocytes and its use may lead to erroneous interpretations of cell binding experiments.